Answer the question

In order to leave comments, you need to log in

T

T

tupoi2015-09-16 19:09:03

3 * 2 = 4 how can you get?

Good day to all, the teacher gave the task of logic 3 times 2 equals 4 (3 * 2 = 4) how can I get this?

there is an option like this

(60-60) = (40-40)

6*(10-10) = 4*(10-10)

6=4

3*2=4

but I would like to play it safe and look at other possible options, otherwise I can’t believe that such an easy solution pulls on the machine, if anyone has ideas, then please write)

a question on logic

Answer the question

In order to leave comments, you need to log in

8 answer(s)

@tupoi

@DmitryITWorksMakarov

@hronik87

@Danand

If "programming" confuses, then*variables* can be understood as the number of some objects.

For example, "three-thirds of an apple is multiplied by two, and four halves of apples are obtained", i.e.

@stetson

B

bubbleboom, 2015-09-17 @tupoi

I'm the only one sure that the question in the original including the correct meaning - ANOTHER?

The TC has the operation of multiplying 2 numbers and it turns out that you need to beat **someone** with a shovel along the ridge before he shows his disrespect for Pythagoras.

The question pulls on the machine for visiting traumatology. Sector prize on the reel...

prove that (3*2) = 4

=> 6 = 4

Here's a variant without extracting the roots, but with quite intense juggling of mathematical expressions.

Let c = a + b, where a and b are any numbers.

a2 - b2 = (a - b) (a + b)

Since c = a + b, we get the identity: a2 - b2 = (a - b) c

Expand the brackets: a2 - b2 = ac - bc

Add the product ab to both parts : a2 + ab - b2 = ac - bc + ab

Move right b2: a2 + ab = ac - bc + ab + b2

Move left ac: a2 + ab - ac = ab - bc + b2

Small grouping: a (a + b - c) = b (a + b - c)

We reduce the expressions in brackets: a = b

Since a and b are arbitrary numbers, it turns out that any number is equal to any number. Indeed, a trick that is quite common among cheaters and mathematicians is used here - juggling. The answer is adjusted to the condition of the problem.

D

Dmitry Makarov, 2015-09-17 @DmitryITWorksMakarov

In general, you can redefine the operation of multiplication. Historically, multiplication is taking the first number a second number of times. And we will agree with you and no one will be able to interfere with this, that when multiplying, it will be necessary to take a tax on the operation in the amount of a third of the result, then:

3 * 2 = 4

3 * 3 = 6

6 * 6 = 24

S

Stalker_darkway, 2015-09-17 @hronik87

How is it that 6=4? Get a drug addict.

6*(10-10) = 4*(10-10)

0 = 0,

not 6=4

A

Andrey Danilov, 2015-09-17 @Danand

If we assume that 3, 2 and 4 are variables, then we can do the following:

```
число 3 = 1; // Также можно поставить 0 или любое число.
число 2 = 1; // Также можно поставить любое число или 0.
число 4 = 1; // Можно поставить 0.
Если(3 * 2 == 4)
ВсёСходится();
```

If "programming" confuses, then

For example, "three-thirds of an apple is multiplied by two, and four halves of apples are obtained", i.e.

`(3 * (1 / 3)) * 2 == 4 * (1 / 2); // 2 == 2`

S

stetson, 2015-09-24 @stetson

Each logical construction is true only within a certain representation. In this case, the problem can be solved as follows - to choose a representation in which the statement "3 times 2 equals 4" is true. Finding such a representation is, of course, easy, for example, by assuming that it is a password.

Similar questions

Y

Z

P

V

P

Didn't find what you were looking for?

Ask your questionAsk a Question

731 491 924 answers to any question